PROJECT ECONOMIC EVALUATION OF LOW PERMEABILITY RESERVOIR DEVELOPMENT USING DISCOUNTED CASH FLOW METHOD AND REAL OPTION ANALYSIS FOR INVESTMENT DECISION - Agus Rudiyono (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
The oil potential from low quality reservoir of Field “X” is big and current recovery is not optimum yet. The typical low quality reservoir with low permeability characteristic is commonly not optimum if it is developed using common vertical well and horizontal well. These methods give low fluid rate deliverables that impact on low recovery and also operational challenges on artificial lift performance since not working on optimum range condition. To improve production performance and recovery, it is required the advanced method such as horizontal drilling using hydraulic multi step fracturing. However horizontal drilling using hydraulic multi step fracturing method need higher capital expenditure and more complex operational aspect during execution. On the current oil price condition, it is required comprehensive investment analysis for decision analysis consideration by performing oil price and investment cost sensitivity analysis, development scenario whether it is delay option, call option or put option. This research performs economic analysis using both Cost recovery PSC system and Gross Split PSC system. For economic analysis method, it use conventional Discounted Cash Flow (DCF) and Real Option to understand the value of flexibility that important for decision consideration.The economic analysis of low permeability reservoir development for 6 wells indicate that this project need 17.6 MM US capital expenditure, and will recover oil volume around 1.89 MMBO. Economic evaluation using DCF method with discount rate 10.8% indicate the economic indices for PSC Cost recovery (NPV = 6.08 MM US, IRR= 28.9%, POT= 0.997 years, PI= 1.28 and Value Creation (VC) 10.65 MM US) and for PSC Gross Split (NPV = 10.64 MM US, IRR= 29.0%, POT= 1.517 years, PI= 1.49 and value creation (VC) 1.94 MM US). Economic analysis using Real Option method with Black Scholes Merton (BSM) indicate that this project will deliver call option value around 9.8 MM US with value of flexibility around 3.7 MM US for PSC cost recovery. Meanwhile Real Option analysis for PSC gross split gives call option value around 10.7 MM US and value of flexibility around 4.1 MM US. The 2 (two) methods recommend that this project economically feasible and suggest to execute the project as planned schedule (call to expand). According to the operational and economic assumption, it is suggested that Gross Split PSC system is potentially better on economic outcome than PSC cost recovery for the contractor (KKKS).